Pengembangan Permainan BOGO (Bola Tangan & Gobak Sodor) untuk Peserta Didik Sekolah Dasar Kelas Atas di SD Kecamatan Tanjunganom Kabupaten Nganjuk - Hardiyanto, Lucky Prasetyo; Herpandika, Reo Prasetiyo; Pratama, Budiman Agung (MAN Insan Cendekia Jambi, 2025)
This study aims to develop a handball game, by collaborating between handball and the traditional gobak sodor game that is already known by students under the name